Pop-up Polanyi: Cultural entrepreneurs and the ‘vacancy fix’ - Scott, Michael; Szili, Gerti (City, Culture and Society, 2017)
Gentrification as an urban strategy pivots upon the dual mediation of the city as a site for aesthetic consumption and pleasure, and as a space of potential ground rent. The recent rise of urban regeneration programs that assist small scale cultural entrepreneurs into disused commercial property – ‘pop-up shops’ – is one example of the convergence of the urban cultural economy and gentrification. This article presents a preliminary explanation of the function of such urban programs through Karl Polanyi's socioeconomic concepts and the case of Renew Adelaide. It is argued that Renew aligns and then stabilises different Polanyian modes of economic integration (reciprocity, redistribution, and exchange), while inducing a partial and temporary de-commodification of urban space. This approach outlines how ‘pop-up’ programs contain multiple objectives. First, they induce the images of creative city vibrancy that can be folded into contemporary place marketing. Second, they enable celebrated entrepreneurial subjectivities to be performed. Third, they illustrate how ‘vacancy fixes’ are addressed via small-scale cultural projects supporting land banking for the owners of properties whose rent gaps have yet to be closed. This Polanyian approach explains how the modes of integration undergirding these programs are assembled via an orientation to the real or symbolic processes of gentrification.
Keywords: creative cities; cultural entrepreneurs; gentrification; modes of economic integration; pop-up; rent gap

Commodifying art, Chinese style: The making of China’s visual art market - Zhang, Jun (Environment & Planning A, 2017)
The economic value of art to cities and regions has recently been vigorously pursued and actively studied. The rapid ascendance of China as a superpower in the global art market and associated transformation of China’s art space, however, are yet poorly understood. This paper develops a Polanyian framework to interpret the spatial and institutional evolution of China’s art market, seeing the (de)commodification of art as a cumulative process embedded in geo-historical interplays of triple logics—cultural, capital, and political, unfolding within, and reshaping in turn, historically inherited spatial structures.
Keywords: China; Chinese art; art - economic aspects; art industry; art market; commodification; cultural and creative industries; public art spaces

Earth Incorporated: Centralization and Variegation in the Global Company Network - Haberly, Daniel; Wójcik, Dariusz (Economic Geography, 2017)
Over the past twenty years, a widening gulf has appeared between the increasingly internationalized financing arrangements of the world’s leading corporations and the persistence of nationally compartmentalized approaches to the study of corporate control. In lieu of direct empirical evidence on corporate control at the global level, the most widespread assumption is that the globalization of ownership has taken the form of an expansion of arm’s-length, market-based arrangements traditionally prevailing in the Anglo-American economies. Here, however, we challenge this assumption, both empirically and conceptually. Empirically, we show that three-quarters of the world’s 205 largest firms by sales are linked to a single global company network of concentrated (5 percent) ownership ties. This network has a hierarchically centralized organization, with a dominantglobal network coreof US fund managers ringed by a more geographically diversestate capitalist periphery. Conceptually, we argue that the this architecture can be broadly explained through a Polanyianvariegated capitalistmodel of contradictory market institutionalization, with the formation of the global company network actually a counterintuitive product of global financial marketization. In order to understand this process of network formation, however, it is necessary to extend Polanyi’s model of a double movement, mediated through political interventions in the market, to incorporate Veblenian processes of evolutionary institutional change, mediated through the market.
Keywords: asset management; asset management concentration; corporate ownership internationalization; evolutionary economic geography; evolutionary economics; financialization; global company network; globalization; sovereign wealth funds; state capitalism; stock ownership; variegated capitalism

Reproducing spaces of embeddedness through Islamic NGOs in Sub-Saharan Africa: reflections on the post-2015 development agenda - Tok, M. Evren; O’Bright, Ben (African Geographical Review, 2017)
This paper explores the nexus of religion, space, and development. It sheds light on the role of faith-based organizations (FBOs) as partners in sustainable development and key actors for achieving the Sustainable Development Goals in sub-Saharan Africa (SSA). Applying and building on the theoretical framework of Polanyi’sThe Great Transformationindicates that FBOs with value-laden agendas have formed new state spaces during the age of globalization, where state capacities are transferred to non-state actors at other levels. The case study of Qatari organizations in SSA demonstrates how their uptake of state capacities can lead to development efforts that are driven by faith apart from politics and economics, which help balance market liberalism and social protectionism to create the conditions for sustainable development. Among other things, FBOs offer alternative financing options and new opportunities for financial inclusion that are relevant to the implementation of the post-2015 development agenda.
Keywords: Africa; Qatar; development; economic development; embeddedness; faith based NGOs; faith based human services; state spaces; sustainable development

From supply management to agricultural subsidies—and back again? The U.S. Farm Bill & agrarian (in)viability - Graddy-Lovelace, Garrett; Diamond, Adam (Journal of Rural Studies, 2017)
Farm subsidies have become increasingly maligned in agricultural policy debates, but the merits of subsidies are a distraction from deeper political, economic, and ecological problems in agriculture. Drawing on a history of the U.S. Farm Bill, this paper argues that a fixation on farm subsidies ignores why they came into being, and more generally glosses over the imperative for modern states to intervene into agricultural economies. Karl Polanyi's 'double movement' framework is used to situate the rise and fall of agricultural supply management within food regime theory. In the second, or surplus food regime, the U.S. government wielded excess commodities as geopolitical tools—even as domestic farm policy labored to contain overproduction, and thus support agrarian viability. In the subsequent corporate food regime, “free market” agriculture displaces and discredits supply management, even as massive government intervention into how food is grown and sold continues. Making space to remember historical price support programs, to situate their accomplishments and limitations, and to recognize residual supply-management mechanisms (such as farm cooperatives and agricultural marketing orders) is crucial for fostering agricultural viability in the US and beyond. Twentieth century supply management had flaws, but it cannot be wholly omitted. This paper highlights key motivations, elements, and contradictions of these policies and programs to begin the process of considering how supply management principles and strategies could be updated and enhanced for 21st century agriculture. Such a framework would need to pay more attention to diversity within domestic and international agricultures, and be more sensitive to the multi-scalar dimensions of food systems.
Keywords: agricultural economics; agricultural subsidies; agriculture & state; business food service; food supply